Efforts to Reduce Carbon Emissions in Rural Areas through Household Waste Management - Fera Widyanata; Vinny Dwi Melliny; Ahmad Syathiri (PT. Altaf Publishing Corp, 2025)
This community service initiative stems from the issue of inadequate domestic waste management in the village of Sakatiga, specifically in the Raudatul Ulum Pesantren area, Ogan Ilir Regency, South Sumatra. This community service aims to raise awareness among the local population that waste management issues are not truly resolved at the landfill site. It also seeks to inform the community that carbon emissions, climate change, and global warming are also consequences of poor waste management. Therefore, the residents must actively maintain environmental cleanliness productively and sustainably. By employing experiential learning and practical application methods, The activity was carried out through several stages, including socialisation and educational sessions, interactive discussions, training, and hands-on field practice in simple domestic waste management techniques, such as waste segregation and proper treatment of different waste types. The community service quite successfully encouraged the local residents to start segregating and managing their household waste more effectively and sustainably. Thus, the pollution and carbon emissions around the village were reduced, contributing to a cleaner and healthier environment.